2004
DOI: 10.1016/j.femsim.2004.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial products increase expression of the human cathelicidin hCAP-18/LL-37 in cultured human sinus epithelial cells

Abstract: The respiratory epithelium plays a major role in the primary defense of the airways against infection. It has been demonstrated that bacterial products are involved in the induction of inflammatory reactions of the upper airways. Little is known about the effects of bacterial products on expression of the antimicrobial peptide hCAP-18/LL-37, the only human cathelicidin identified so far. The aim of this study was to investigate the effects of bacterial products from both gram-positive and gram-negative bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…These bacterial effects on LL-37 expression were suggested to be mediated via bacterial DNA [17]. Nell et al demonstrated the increased expression of cathelicidin in nasal sinus epithelium in inflammation and the relationship with inflammation via stimulation of IL-8 released by epithelial cells [18]. In this study, we demonstrated that the chronic tonsillar inflammation upregulates the expression of cathelicidin in tonsillar epithelium.…”
Section: Discussionsupporting
confidence: 59%
“…These bacterial effects on LL-37 expression were suggested to be mediated via bacterial DNA [17]. Nell et al demonstrated the increased expression of cathelicidin in nasal sinus epithelium in inflammation and the relationship with inflammation via stimulation of IL-8 released by epithelial cells [18]. In this study, we demonstrated that the chronic tonsillar inflammation upregulates the expression of cathelicidin in tonsillar epithelium.…”
Section: Discussionsupporting
confidence: 59%
“…CAMP expression can be induced by 1,25-dihydroxyvitamin D3 (13), pathogens (9), or lipopolysaccharide (LPS) (14). Decreased CAMP/LL-37 production accompanies increased invasion and colonization by pathogens in epithelial cells, which characterizes diseases such as morbus Kostmann (15) and atopic dermatitis (16).…”
mentioning
confidence: 99%
“…In addition, it exhibits chemotactic properties and plays a role in dendritic cell maturation, identifying it as an important mediator in the innate and adaptive immune systems (reviewed in reference 6). LL-37 gene expression can be induced by live bacteria (36) or by bacterial products such as lipopolysaccharide (LPS) (30,39), and the active LL-37 peptide is processed from the inactive human CAP-18 (hCAP-18) precursor by proteolysis. Lack of LL-37 is associated with two human disorders, morbus Kostmann and Papillon-Lefèvre syndrome, in which there is severe periodontal disease associated with colonization by the periodontal pathogen Aggregatibacter actinomycetemcomitans (8,11,41).…”
mentioning
confidence: 99%
“…Lack of LL-37 is associated with two human disorders, morbus Kostmann and Papillon-Lefèvre syndrome, in which there is severe periodontal disease associated with colonization by the periodontal pathogen Aggregatibacter actinomycetemcomitans (8,11,41). LL-37 gene expression can be induced by live bacteria (36) or by bacterial products such as LPS (30,39), making the peptide part of the innate immune defense of the gingival epithelium.…”
mentioning
confidence: 99%